Thermophysical properties and Optimization of modified palm Oil-Amine reinforced biocomposites for lightweight and insulating applications - Sahal, Hakan; Aydogmus, Ercan; Arslanoglu, Hasan (Elsevier, 2025)
The aim of this study is to investigate various thermophysical properties of modified palm oil-amine (MPOA) reinforced biocomposites to optimize these materials to meet the requirements of lightness and insulation. The effects of MPOA addition to biocomposites on bulk density, surface hardness, thermal conductivity coefficient, and activation energy have been evaluated. In addition, the structural and physical properties of these biocomposites are aimed to determine their potential use as lightweight and thermal insulation materials. The results show that MPOA incorporation significantly affects the bulk density, Shore A hardness, thermal conductivity, and thermal stability of biocomposites. The addition of MPOA provides significant benefits for lightweight biomaterials by reducing bulk density. However, high MPOA content decreases the surface hardness of the biocomposite, and with zirconium silicate (ZrSiO4), this drawback is eliminated and the curing time is reduced. Increasing MPOA ratios also improve the insulation properties of biocomposites by reducing the thermal conductivity coefficient. Thermal decomposition experiment results show that higher MPOA content reduces thermal stability. Scanning electron microscopy (SEM) reveals that high levels of MPOA lead to increased surface porosity and irregularities, negatively affecting surface morphology. An optimal MPOA reinforcement level of 5 wt% provides a balance between desirable properties such as reduced density and improved thermal insulation while minimizing adverse morphological effects. Fourier-transform infrared spectroscopy (FTIR) confirms the presence of epoxy resin and the successful chemical modification of palm oil to create bioepoxy feedstock. MPOA reinforcement offers benefits such as reduced bulk density and improved thermal insulation while addressing challenges in surface morphology, mechanical properties, and thermal stability. The study concludes that biocomposites with 5 wt% MPOA provide optimum stability, making them suitable for applications requiring lightweight and thermally insulating materials without significantly compromising structural integrity. This research, the long-term performance of biocomposites, and future investigations into their potential applications will further expand their practical applicability.
Keywords: Modified palm oil-amine; Zirconium silicate; Biocomposite; Optimum stability; Thermophysical properties